Clinical and Genetic Aspects of CADASIL - Mizuno, Toshiki; Mizuta, Ikuko; Watanabe-Hosomi, Akiko; Mukai, Mao; Koizumi, Takashi (Frontiers in Aging Neuroscience, 2020)
CADASIL, a hereditary, cerebral small-vessel disease caused by mutations in NOTCH3, is characterized by recurrent cerebral ischemic events without vascular risk factors, mood disturbances, and dementia. MRI imaging shows cerebral white matter hyperintensity, particularly in the external capsule and temporal pole. Missense mutations related to cysteine residue in one of the 34 EGFr in the NOTCH3 receptor are typical mutation of CADASIL. On the other hand, atypical mutations including cysteine sparing mutation, homozygous mutation and other associate genes are also reported. From the view point of gain of function apart from Notch signaling or loss of function of Notch signaling, we review the research article about CADASIL and summarized the pathogenesis of small vessel, stroke and dementia in this disease.